Transcriptional and reverse transcriptional regulation of host genes by human endogenous retroviruses in cancers - Zhang, Mengwen; Zheng, Shu; Liang, Jessie Qiaoyi (Frontiers in Microbiology, 2022)
Human endogenous retroviruses (HERVs) originated from ancient retroviral infections of germline cells millions of years ago and have evolved as part of the host genome. HERVs not only retain the capacity as retroelements but also regulate host genes. The expansion of HERVs involves transcription by RNA polymerase II, reverse transcription, and re-integration into the host genome. Fast progress in deep sequencing and functional analysis has revealed the importance of domesticated copies of HERVs, including their regulatory sequences, transcripts, and proteins in normal cells. However, evidence also suggests the involvement of HERVs in the development and progression of many types of cancer. Here we summarize the current state of knowledge about the expression of HERVs, transcriptional regulation of host genes by HERVs, and the functions of HERVs in reverse transcription and gene editing with their reverse transcriptase.